10 years [videorecording (DVD)] - Collins, Lynn, 1977-; Dawson, Rosario; Dewan, Jenna, 1980-; Geraghty, Brian; Graynor, Ari; Isaac, Oscar; Livingston, Ron; Long, Justin, 1978-; Mackie, Anthony, 1978-; Mara, Kate, 1983-; Minghella, Max, 1985-; Plaza, Aubrey, 1984-; et al. (Anchor Bay Films, 2012)
The night before their high school reunion, a group of friends realize they still haven't quite grown up in some ways.